Nowe kostki mozaikowe z Ostrowa Tumskiego w Poznaniu, stan. 13 - Jankowiak, Dominika; Lech, Paweł; Sikorski, Andrzej (Folia Praehistorica Posnaniensia, 2012)
Between 1950 and 2010, the central and southern parts of the fortified settlement in Poznań yielded over 280 glass mosaic cubes – tesserae, dated to the 11th till 13th century (the largest collection of such decorative elements in Poland). The western part of the site Ostrów Tumski 13 (OT 13), produced two more cubes. The cubes (one translucent and gilded, the other one red) probably come from the destroyed palatial-sacral complex, or from the cathedral, or any other building in the area.